2019
DOI: 10.1111/pde.13808
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis to chlorhexidine in pediatric patients

Abstract: Chlorhexidine is one of the most widely used antiseptics in our environment. Allergic contact dermatitis to chlorhexidine is common in adults, but is quite rare in the pediatric population. Its diagnosis is important because it can mimic other dermatoses common during childhood, and it can also lead to acute immediate hypersensitivity | 541 Pediatric Dermatology BRIEF REPORT undiagnosed. 1 Only 4 cases have been reported of ACD to chlorhexidine in pediatric patients without underlying AD. 3-5 Darrigade et al r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…A potential adverse effect of this antimicrobial agent is allergic contact dermatitis. 54 The Infectious Diseases Society of America published guidelines for the management of recurrent SSTI because of MRSA in 2011. 55 Similar principles apply to the management of recurrent SSTI in AD.…”
Section: Prevention Of Infections In Admentioning
confidence: 99%
“…A potential adverse effect of this antimicrobial agent is allergic contact dermatitis. 54 The Infectious Diseases Society of America published guidelines for the management of recurrent SSTI because of MRSA in 2011. 55 Similar principles apply to the management of recurrent SSTI in AD.…”
Section: Prevention Of Infections In Admentioning
confidence: 99%
“…In Europe, one of the most widely employed antiseptics is chlorhexidine digluconate, both in aqueous and alcohol solutions. It is also used as an antimicrobic compound in numerous drugs and cosmetics 1‐3 . Allergic contact dermatitis (or ACD) in response to chlorhexidine is common in adults, with a prevalence of about 1%, but is rare in pediatric patients 3,4 …”
Section: Discussionmentioning
confidence: 99%
“…Anaphylaxis has been reported as a severe immediate immunoglobulin E (IgE)–mediated reaction to chlorhexidine after medical operations 5,6 . Although the incidence of ACD in response to chlorhexidine in the pediatric population is considered very low, some studies demonstrated that the prevalence of chlorhexidine sensitization occurs in about 2.9% in patients younger than 16 years of age with atopic predisposition 1,3 . Early use of chlorhexidine (particularly during surgery) could determine sensitization during the first years of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During house cleaning, the use of nitrile gloves and a proper rinse of the contact surfaces may be useful. In case of worsening or suspicion of superinfection, it is advisable to contact the family doctor for further therapies [19][20][21][22][23].…”
Section: Atopic Dermatitismentioning
confidence: 99%